Insect Hormones - Litwack, Gerald (Vitamins and hormones ;, 2005)
Insect biochemistry and molecular genetics have become enormously important sciences. Molecular genetics of drosophila has paced mammalian genetics and has facilitated many advances in mammalian genetics. Moreover, many life-threatening diseases for man are now carried chiefly by insects and our increasing knowledge of the basic science of insects may help to control these diseases. There is no more important facet of insect science than insect hormones, the agents that allow for communication between cells and tissues. This volume updates important areas of this subject, namely: hormonal control of ecdysis; ecdysone receptors in agriculture and medicine; molecular structure of the receptor ligand binding site of ecdysone; a molecular genetic approach to the biosynthesis of the molting hormone; non-steroidal ecdysone agonists; molecular actions of juvenile hormone in drosophila, and insect neuropeptide receptors.